2019
DOI: 10.3390/antiox8080278
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, Anti-Inflammatory, and Anticancer Effects of Purified Flavonol Glycosides and Aglycones in Green Tea

Abstract: (1) Background: Extensive research has focused on flavan-3-ols, but information about the bioactivities of green tea flavonols is limited. (2) Methods: In this study, we investigated the antioxidative, anti-inflammatory, and anticancer effects of flavonol glycosides and aglycones from green tea using in vitro cell models. The fractions rich in flavonol glycoside (FLG) and flavonol aglycone (FLA) were obtained from green tea extract after treatment with tannase and cellulase, respectively. (3) Results: FLG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 52 publications
1
55
0
1
Order By: Relevance
“…Recent studies have also found triglycosides of myricetin and have defined their disappearance as a consequence of the fermentation and oxidation processes [46]. Recently, the obtainment of a flavonol glycosides-rich extract named FLG was optimized from an aqueous green tea extract after tannase treatment [47]. Apigenin-C-mono-and diglycosides, as well as some different mono-and diglycosides of flavonols myricetin, quercetin, and kaempferol were detected.…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 99%
“…Recent studies have also found triglycosides of myricetin and have defined their disappearance as a consequence of the fermentation and oxidation processes [46]. Recently, the obtainment of a flavonol glycosides-rich extract named FLG was optimized from an aqueous green tea extract after tannase treatment [47]. Apigenin-C-mono-and diglycosides, as well as some different mono-and diglycosides of flavonols myricetin, quercetin, and kaempferol were detected.…”
Section: Chemical Composition Of Alcoholic Extracts From Commercializmentioning
confidence: 99%
“…GTE was prepared according to the method described by Rha et al [30]. Briefly, GT (Osulloc Farm Corp., Seogwipo, Republic of Korea) was harvested from May-June, 2017, and then processed into a loose tea.…”
Section: Preparation Of Gtementioning
confidence: 99%
“…The numbers 1-13, 14, 15, and 16 indicate flavonol glycosides, myricetin, quercetin, and kaempferol, respectively. Refer to the exact mass and structural information of numbered peaks in previous research[30].…”
mentioning
confidence: 99%
“…Protective effects of the green tea components against FDP-induced damage Recently, we isolated GTE, fractions rich in FLGs, and CTPs from green tea leaves as bioactive ingredients [45,46]. Because phenolic compounds from various plants have been shown to exert protective effects against FDP-induced oxidative stress and in ammation in skin cells [47,48,49] and because green tea polysaccharides exhibit bene cial antioxidant [50], antitumor [36], and antiaging properties [51], we hypothesized that green tea polyphenols and polysaccharides could also ameliorate FDP-induced cellular damage in the airway.…”
Section: Fdps Induce Oxidative Damage and Cell Death In Airway/lung Cmentioning
confidence: 99%
“…The chemical properties of GTE, FLGs, and CTPs were investigated. As shown in Table 1 [46]. In addition, the CTPs included mainly pectic substances and glucosidic macromolecules found in unligni ed cell walls, major components of the middle lamellae in plants [45]; these pectic polysaccharides have various pharmacological properties [30,52,53].…”
Section: Fdps Induce Oxidative Damage and Cell Death In Airway/lung Cmentioning
confidence: 99%